Gizi Seimbang, Tumbuh Kembang Pasti dengan Daun Kelor (GISEDA) di Desa Talaga Tomoagu - Rifani Hutami Supardi; Muhammad Rafiq Lakali; Miftahul Jannah Amala; Putri Novtafia Lahay; Devara Tilli; Billy Pratama Damopolii; Astari Aprillia Mariama; Maria Cicilia Riandi (Aksi Nyata : Jurnal Pengabdian Sosial dan Kemanusiaan, 2025)
One of the health issues in Talaga Tomoagu village, Bolangitang Barat district, North Bolaang Mongondow regency, is stunting or slow growth in children of the same age, which remains high. Based on data from the Talaga Tomoagu village Health Office, the prevalence of stunting in 2022 was 1.82%, in 2023 it increased to 5.08%, and in 2024 it further increased to 6.67%. Cases of stunting in children and toddlers are a common issue that needs to be addressed in Indonesia due to the lack of balanced nutritional intake. The aim of this program is to provide innovative healthy nutrition menus with children's food preparations (nuggets) made from moringa leaves to prevent stunting. The method used in this program is to provide direct educational counseling and demonstrations on making moringa leaf-based complementary food nuggets. The results of this innovative program show that education on healthy nutrition menus affects mothers' knowledge about stunting and its prevention efforts. After being provided with education and training on making food based on moringa leaves, the results significantly influenced the mothers' knowledge about balanced nutrition as a prevention of stunting issues in the village of Talaga Tomoagu.